The role of cyclooxygenase‐2 and prostaglandin E2 in the pathogenesis of cutaneous lichen planus. (1st December 2015) - El‐Rifaie, A. A.; Rashed, L. A.; Doss, R. W.
Summary: Background: Lichen planus (LP) is an inflammatory disease of the skin and mucous membranes. Autoimmunity has been suggested as a possible cause of this disease. The cyclooxygenase enzymes (COX‐1, COX‐2) are the key enzymes in the conversion of arachidonic acid into prostaglandins. Prostaglandin E2 (PGE2), a key product of COX‐2, has an immunomodulatory role. Aim: To map levels of COX‐2 and PGE2 in cutaneous LP lesions and evaluate their role in the pathogenesis of the disease. Methods: In total, 31 patients with classic cutaneous LP and 30 age‐ and sex‐matched healthy controls were enrolled. Skin biopsies were taken from the lesional and nonlesional skin of patients, and from the normal skin of controls. COX‐2 mRNA expression was detected by real‐time reverse transcription quantitative PCR, and PGE2 was detected by ELISA in skin biopsies from patients and controls. Results: Our analysis revealed a significantly higher expression of COX‐2 mRNA and PGE2 in the LP skin biopsies compared with the control biopsies ( P < 0.001 and P < 0.001, respectively). Lesional biopsies showed significantly higher expression of COX‐2 mRNA and PGE2 compared with nonlesional biopsies. The levels of COX‐2 and PGE2 were not found to be correlated with age, sex or disease duration. Conclusions: COX‐2 and its product PGE2 are strongly expressed in LP skin lesions, indicating that they have a role in the pathogenesis of LP through their immunomodulatory effects.